2014
DOI: 10.1063/1.4899042
|View full text |Cite
|
Sign up to set email alerts
|

Influence of insulating coating on aluminum wire explosions

Abstract: Single wire explosions are widely used in understanding the early stages of z-pinch experiments. This paper presents a serial of experiments conducted on the pulse power generator with $1 kA peak current and $10 ns rising time in Xi'an Jiao Tong University. Polyimide coated aluminum wires and uncoated ones were tested under three different voltages to analyze the effect of insulating coating. Experimental results showed that insulating coating can increase the energy deposition 10%$30% in aluminum wires by del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…According to [178], the core expansion velocity at (d I/dt) av = 150 A/ns was (3-6) • 10 5 cm/s for bare wires made of Au, Cu, Ag, and Al and (0.4-1) • 10 5 cm/s for bare wires made of W, Mo, and Pt. Shi et al [19], Rousskikh et al [123], Zhao et al [172], Wu et al [173], [174], and Li et al [184] measured v core values similar to those reported in [168] and [178].…”
Section: B Core Structure (Core Expansion and Stratification And Micr...supporting
confidence: 55%
See 2 more Smart Citations
“…According to [178], the core expansion velocity at (d I/dt) av = 150 A/ns was (3-6) • 10 5 cm/s for bare wires made of Au, Cu, Ag, and Al and (0.4-1) • 10 5 cm/s for bare wires made of W, Mo, and Pt. Shi et al [19], Rousskikh et al [123], Zhao et al [172], Wu et al [173], [174], and Li et al [184] measured v core values similar to those reported in [168] and [178].…”
Section: B Core Structure (Core Expansion and Stratification And Micr...supporting
confidence: 55%
“…The experiments [19], [123], [172]- [175], [184] also demonstrated the effectiveness of increasing (d I/dt) av as a means of increasing the energy input into the wire. Table III shows the experimentally obtained values of ε dep /ε atom reported by various authors for W wires exploded at different values of (d I/dt) av .…”
Section: A Deposited Energymentioning
confidence: 81%
See 1 more Smart Citation
“…The gasification of single wires has been investigated, including by short, nanosecond length current pulses. Aluminum wires were relatively easy to be heated to a gaseous state due to their low atomization entropy, low electron emissivity, and the aluminum oxide layer covered on the surface of the wire, 7,8 while the gasification of the high-Z refractory elements was more difficult. With the help of insulated coatings, the atomization of the high-Z materials (e.g., tungsten and platinum) has been fulfilled partially.…”
mentioning
confidence: 99%
“…Al nanoparticles have important applications in a variety of fields, e.g. explosives [13], propellants [14][15][16], electronics [17] and detection of biomolecules [18]. Lerner et al [19] investigated the electrical explosion process of Al wires in Ar and N, and synthesized Al and Al/AlN composite nanoparticles.…”
Section: Introductionmentioning
confidence: 99%